CD36 Deficiency Inhibits Retinal Inflammation and Retinal Degeneration in Cx3cr1 Knockout Mice - Lavalette, Sophie; Conart, Jean-Baptiste; Touhami, Sara; Roubeix, Christophe; Houssier, Marianne; Augustin, Sébastien; Raoul, William; Combadière, Christophe; Febbraio, Maria; Ong, Huy; Chemtob, Sylvain; Sahel, José-Alain; et al. (Frontiers in Immunology, 2020)
Background: CD36, a member of the class B scavenger receptor family, participates in Toll-like receptor signaling on mononuclear phagocytes (MP) and can promote sterile pathogenic inflammation. We here analyzed the effect of CD36 deficiency on retinal inflammation and photoreceptor degeneration, the hallmarks of age-related macular degeneration (AMD), that characterize Cx3cr1-/-mice, Methods: We analyzed subretinal MP accumulation, and cone- and rod-degeneration in light-challenged and aged, CD36 competent or deficient, hyper-inflammatory Cx3cr1-/- mice, using histology and immune-stained retinal flatmounts. Monocytes (Mo) were subretinally adoptively transferred to evaluate their elimination rate from the subretinal space and Interleukin 6 (IL-6) secretion from cultured Mo-derived cells (MdCs) of the different mouse strains were analyzed. Results: CD36 deficient Cx3cr1-/- mice were protected against age- and light-induced subretinal inflammation and associated cone and rod degeneration. CD36 deficiency in Cx3cr1-/- MPs inhibited their prolonged survival in the immune-suppressive subretinal space and reduced the exaggerated IL-6 secretion observed in Cx3cr1-/- MPs that we previously showed leads to increased subretinal MP survival. Conclusion: Cd36 deficiency significantly protected hyperinflammatory Cx3cr1-/- mice against subretinal MP accumulation and associated photoreceptor degeneration. The observed CD36-dependent induction of pro-inflammatory IL-6 might be at least partially responsible for the prolonged MP survival in the immune-suppressive environment and its pathological consequences on photoreceptor homeostasis.